Efeitos cardiovasculares do óleo essencial de Lippia alba (Mill) N.E. Brown. (Erva Cidreira Brasileira) em ratos - Maynard, Luana Godinho (2011)
Lippia alba (Mill.) N.E. Brown (VERBENACEAE), popularly know as Erva Cidreira Brasileira, has been one of the most commonly herbs used in the Brazilian folk medicine to blood pressure control. This study aimed to investigate the cardiovascular effects of the essential oil of Lippia alba (EOLA) in rats. For the hemodynamic measurement, normotensive male Wistar rats had their abdominal aorta and lower vena cava cannulated. Initially, five chemotypes (geranial, limonene, linalool, mircene, and carvone) were tested in normotensive conscious rats. They were intravenously and in bolus administrated at the doses of 5, 10, 20, 40 and 60 mg/kg. The EOLAG showed the best results on blood pressure, being chosen for the following experiments. The administration of EOLAG (5, 10, 20, and 40 mg/kg, i.v.) induced transient hypotension and bradycardia. These responses were attenuated by atropine (2 mg/kg, i.v.), hexamethonium (20 mg/kg, i.v.) and NG-nitro-Larginine methyl ester hydrochloride (L-NAME - 20 mg/kg, i.v.), but not by indomethacin (5 mg/kg, i.v.). For in vitro approach, the rats were euthanized and the superior mesenteric artery was removed and cut in rings (1-2 mm), which were placed in organ baths containing Tyrode`s solution at 37o C and gassed with carbogen. In intact rings of rat mesenteric artery pre-contracted with phenilephrine (1 μM), EOLAG (1 - 1000 mg/mL) induced relaxation (pD2 = 1.89 ± 0.21; Emax = 110.8 ± 10.8 %) which was not modified after the removal of the endothelium (pD2 = 2.37 ± 0.16; Emax = 134.8 ± 16.5 %), after incubation with TEA (pD2 = 2.23 ± 0.04; Emax = 117.2 ± 4.96 %) or KCl (80 mM) (pD2 = 1.96 ± 0.06; Emax = 112.6 ± 6.70 %). In addition, the EOLAG was able to inhibit the contraction caused by CaCl2 and produced additional effect (34.82 %; n = 5) on maximal relaxation of nifedipine (10 μM). In conclusions, the results demonstrate that the EOLAG induces hypotensive effect, that seems to be caused by muscarinic activation and NO release, and bradycardia, that seems to be due to an activation of ganglion nicotinic and cardiac muscarinic receptors. Furthermore, EOLAG produces vasorelaxation primarily caused by blocking Ca2+ influx through voltage-operated Ca2+ channels.